Legal Studies on the Use of Renewable Energy in Environmental Management in Indonesia: A Literature Study - Rakuasa, Heinrich; Latue, Philia Christi (Civiliza Publishing, 2024)
This study highlights the development of research that addresses the potential of renewable energy while identifying gaps in understanding the legal implications and challenges associated with its implementation. The method used in this research is Literature Study. This study emphasizes the importance of an effective legal framework to encourage investment and innovation in renewable energy technologies, as well as the role of local regulations in supporting local initiatives. By integrating renewable energy sources into environmental management strategies, the article argues that Indonesia can address critical environmental issues, such as pollution and biodiversity loss, which will ultimately benefit the environment and people's welfare. The findings aim to contribute to the ongoing discourse on renewable energy policy and its implications for environmental law in Indonesia.